A Study on the Effect of Natural Regenerated and Synthetic Non-woven Fabric Properties on Acoustic Applications. Issue 13 (1st December 2022) - Velayutham, Thirumurugan; Kumar, M. Ramesh; Sundararajan, Paramasivam; Chung, Ill-Min; Prabakaran, Mayakrishnan
ABSTRACT: In this world, unnoticed sound that disturbs frequently is called as noise. It is one of the main reasons for reducing the environment quality of human being. This effect can be minimized by using acoustic absorbent material in different areas where the sound absorption is required. In textile, acoustic property of non-woven is better than the woven fabric. The non-woven fabrics were developed using the needle punching technique using kapok, jute, flax, viscose, polyester, polypropylene, and recycled polyethylene terephthalate (R-Pet) fibers. Sound absorbency parameter was tested by sound absorption tester specially designed for this purpose. The effects of fiber type, number of layers in the fabric, thickness of the sample, areal density, air permeability, and pore size on sound absorption capacity were investigated in this research work. Experimental results show that 100% kapok non-woven fabric with its high compact structure, higher thickness, lesser air permeability, and less average flow diameter exhibit good sound absorption property than other samples, and it is best-suitable for interior in automotive applications for noise control.